1984
DOI: 10.1111/j.1651-2227.1984.tb09969.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function and Oxygen Uptake During Exercise in 16 Year Old Boys with Cystic Fibrosis

Abstract: Eight of altogether 9 Norwegian boys with cystic fibrosis (CF), aged 15-17 years, and 8 healthy boys of the same age underwent pulmonary function and bicycle exercise testing. Although the CF boys showed large individual variations, the two groups showed great differences in mean body height and weight, pulmonary function variables and maximum oxygen uptake. The maximum oxygen uptake for the CF boys ranged from 40 to 125% (mean 79%) of predicted values. Increased ventilatory equivalent for oxygen was a charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 6 publications
4
28
1
Order By: Relevance
“…Several smaller studies have included lactate measurement in the assessment of peak exercise, and have shown that CF subjects do generate a rise in blood lactate on progressive exercise [16][17][18][19]. The present authors found raised lactate levels at peak exercise in CF patients across the full range of pulmonary disease severity, with those in the middle/ moderate group achieving very similar peak concentrations to controls.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Several smaller studies have included lactate measurement in the assessment of peak exercise, and have shown that CF subjects do generate a rise in blood lactate on progressive exercise [16][17][18][19]. The present authors found raised lactate levels at peak exercise in CF patients across the full range of pulmonary disease severity, with those in the middle/ moderate group achieving very similar peak concentrations to controls.…”
Section: Discussionsupporting
confidence: 63%
“…However, there is little data concerning lactate accumulation during exercise in CF, although several small studies in subjects with milder disease have shown that lactate accumulation occurs [16][17][18][19]. There is very little information concerning symptom limitation during exercise in CF.…”
mentioning
confidence: 98%
“…There are several potential explanations for why the equation of Corder et al might be inaccurate for use in children with chronic disease. These include delayed gross motor skill development among children with chronic disease, inefficiency of movement from disease complications, increased resting and AEE associated with heart and lung function (Hjeltnes et al, 1984;Knops et al, 1999;Groen et al, 2010), higher HR for a given VO 2 because of deconditioning (Bar-Or and Rowland, 2004) and altered movement patterns to reduce pain (Broström et al, 2007). Each of these would increase HR and EE for a given activity, which may explain why the equation of Corder et al consistently overestimated AEE (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, airway dead space is independent from V T , thus in cases of reduction in V T the patient has a greater proportion of dead space for each breath. However, several studies in CF patients with mild or moderate pulmonary disease reported increases in lactate levels [125,126,127,128] and early occurrence of the lactate threshold [127] during incremental exercise, indicating an increase in muscle anaerobic metabolism and suggesting that peak exercise is not limited by ventilation, but rather by nonpulmonary factors that lead to leg fatigue. A relatively low V′ E /MVV at peak exercise and high HR reserve supported this interpretation.…”
Section: Exercise Intolerance In Cystic Fibrosismentioning
confidence: 99%